ENRICH: The Developed English Grade 8 Most Essential Learning Competencies-Based and Integration-Focused Worksheets - Margielyn M Angay (Journal of Elementary and Secondary School, 2023)
This paper presents the development and validation of an English Grade 8 Worksheet aligned with the Most Essential Learning Competencies (MELCs) and emphasizing integration across subjects. A quantitative research design was employed to assess these worksheets' content validity and acceptability. The evaluation used simple mean and four-point Likert scales to gauge validity and acceptability. Additionally, a T-test was conducted to determine if there was a significant difference in learner performance between their pretest and posttest. The assessment involved various education professionals, including head teachers, master teachers, subject-specific teachers, and program supervisors. Remarkably, all evaluators unanimously rated the content validity of the worksheets as "Highly Valid," encompassing criteria such as objectives, content, format, language, and presentation. Similarly, the worksheets received unanimous acclaim as "Very Acceptable" regarding functionality, accuracy, suitability, and usability. Statistical analysis revealed a significant improvement in learner performance from the pretest to the posttest, with a probability value below the 0.05 significance threshold. This suggests that the designed instructional material is well-prepared for implementation in the upcoming school year. In conclusion, this study aimed to create and validate English Grade 8 MELCs-based worksheets that seamlessly integrated content from Science and TLE subjects. The research recognized the need for learning materials that effectively blend English with other subjects while adhering to the K–12 MELCs. By developing and validating these integrated worksheets, the study contributes to enhancing English language education, promoting subject integration, and elevating the quality of interdisciplinary instruction.